Níveis de proteína bruta e de energia metabolizável para frangas de postura semipesadas de 1 a 18 semanas de idade - Lima Neto, Raul Da Cunha; Costa, Fernando Guilherme Perazzo; Silva, José Humberto Vilar Da; Barros, Leilane Rocha [UNESP]; Oliveira, Cleber Franklin Silva De; Costa, Janaíne Sena Da (Editora da Universidade Federal de Lavras, 2008)
The aim of this experiment was to evaluate the performance of commercial layers between 1 and 18 weeks of age submitted to different crude protein (CP) and metabolizable energy (ME) levels. The trial was carried out at the poultry sector of the Department of Animal Science, of the Centro de Ciências Agrárias, Universidade Federal of Paraiba, Areia-PB, Brazil. Four hundred and thirty-two Lohmann Brown chicks were used at 3 days of age according to a completely randomized design in a 3 x 3 factorial scheme, with three CP levels and three ME levels. In the first phase (1-6 wk), the birds were fed with diets containing three levels of CP: 21, 22 or 23% CP and three levels of ME: 2,900, 3,000 and 3,100 kcal/kg diet. In the second phase (7-12 wk) and in the third phases (13-18 wk), CP levels of feeding were 18, 19 or 20%, and 16, 17 or 18%, respectively, and three ME levels being 2,700, 2,800 or 2,900 kcal ME/kg diet in these two phases. It was not found interaction between CP and ME levels. Based on the results obtained one recommends for the phases from 1 to 6, 7 to 12 and 13 to 18 weeks of age the levels of 21 % of CP and 2900 kcal of ME /kg diets, 20% of CP and 2700 kcal of ME/kg diets and 16% of CP and 2700 kcal of ME/kg diets respectively.

Objetivou-se neste experimento avaliar o desempenho de poedeiras comerciais de 1 a 18 semanas de idade submetidas a níveis de Proteína Bruta (PB) e de Energia Metabolizável (EM). O experimento foi desenvolvido no aviário de Departamento de Zootecnia do Centro de Ciências Agrárias da UFPB, em Areia-PB. Foram utilizadas 432 pintainhas Lohmann Brown de três dias de idade, distribuídas em um delineamento inteiramente casualizado, em esquema Fatorial 3x3, com três níveis de PB e três níveis de EM. Na primeira fase, de 1 a 6 semanas de idade, as aves foram alimentadas com rações contendo três níveis de PB (21, 22 e 23%) e três de EM (2900, 3000 e 3100kcal/kg de ração). Na segunda e terceira fases, as aves com idades de 7 a 12 e de 13 a 18 semanas, respectivamente, foram alimentadas com três níveis de PB sendo 18, 19 e 20% de sete a doze semanas e 16, 17 e 18% de treze a dezoito semanas e três níveis de EM sendo 2700, 2800 e 2900kcal/kg de ração nessas duas fases. Não foi encontrada interação entre os níveis de PB e de EM. Com base nos resultados obtidos, recomenda-se, respectivamente, para as fases de 1 a 6, de 7 a 12 e de 13 a 18 semanas de idade, os níveis de 21% de PB e 2900 kcal de EM/kg de ração, 20% de PB e 2700 kcal de EM/kg de ração e 16% de PB e 2700 kcal de EM/kg de ração.
Crude protein and metabolizável energy levels for eggy-type pullets from 1 to 18 weeks of age
Keywords: Performance; nutritional requirements; Layers; Desempenho; Exigência Nutricional; Poedeiras